Prevalence and Prognostic Importance of Massive Tricuspid Regurgitation in Patients Undergoing Tricuspid Annuloplasty With Concomitant Left-Sided Valve Surgery: A Study on Rheumatic Valvular Heart Disease - Chen, Yan; Chan, Yap-Hang; Wu, Mei-Zhen; Yu, Yu-Juan; Lam, Yui-Ming; Sit, Ko-Yung; Chan, Daniel Tai-Leung; Ho, Cally Ka-Lai; Ho, Lai-Ming; Lau, Chu-Pak; Au, Wing-Kuk; Tse, Hung-Fat; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The presence of tricuspid regurgitation (TR) is very common in patients with concomitant left-sided valve disease. Recent studies have advocated an additional grading of massive TR that is beyond severe. The present study sought to characterize the spectrum of TR in patients undergoing tricuspid annuloplasty (TA) and to evaluate the prognostic value of TR severity for post-operative outcome following TA. Methods A total of 176 patients who underwent TA with combined left-sided valve surgery, secondary to rheumatic valvular heart disease, were prospectively evaluated. The severity of TR was quantified by effective regurgitant orifice area (EROA) using the proximal isovelocity surface area method. Patients were categorized as having non-massive TR (EROA < 0.6 cm2) or massive TR (EROA ≥ 0.6 cm2). Adverse outcome was defined as all-cause mortality or heart failure requiring hospital admission following TA. Results A total of 55 (31%) patients were considered to have massive TR. Patients with massive TR had a greater right ventricular dimension but a smaller left ventricular dimension compared with those with non-massive TR. After a median follow-up of 39 months, 35 adverse events occurred. Cox-regression analysis showed that both continuous EROA and dichotomized EROA (massive vs. non-massive TR) were independently associated with adverse events even after multivariable adjustment. Further, Harrell C index demonstrated that the addition of massive TR provided better discrimination ability of a prediction model to known prognosticators following TA. Conclusions Massive TR is common and up to 31% of study population had massive TR. Massive TR was associated with adverse outcome in patients undergoing TA. Classification of the severity of TR by quantitative measures and identification of massive TR in patients with concomitant left-sided valve disease are essential when considering the optimal timing of corrective surgery.